Research on thermal barrier and thermal shock resistance of NiCr−mullite composite ceramic coating - CAO Yang; ZHANG Peng-lin; NIU Xian-ming; HU Chun-Lian; CHEN Kai-wang (Fenmo yejin jishu)
Five groups of the NiCr−mullite composite powders in various proportions were mixed by ball milling. The NiCr−mullite composite ceramic coatings on the 45 Steel were prepared by the supersonic plasma spraying. The thermal conductivity and thermal shock resistance of the coatings was tested. The microstructures of the coating surface and cross section were observed by the scanning electron microscope (SEM), the chemical composition in the characteristic area of coatings was analyzed by the energy disperse spectroscopy (EDS), and the phase constitution of the coatings was analyzed by X-ray diffraction (XRD). The results show that, the NiCr solid solution is the matrix of the NiCr−mullite composite coatings, which is uniformly distributed by the mullite particles. The diffusion phases are formed between the mullite particles and the NiCr matrix to improve the wettability, and the mullite particles can be coated firmly by the diffusion phases and the NiCr matrix. Meanwhile, the NiCr matrix can be reinforced by the mullite particles. The strength toughness and the thermal shock resistance of the coatings increase, and the thermal conductivity reduces with the increase of the mullite volume fraction from 38% to 75%.